2003
DOI: 10.1046/j.1365-2761.2003.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the fish‐pathogenic fungus Aphanomyces invadans

Abstract: Aphanomyces invadans (Saprolegniaceae) is a peronosporomycete fungus associated with the serious fish disease, epizootic ulcerative syndrome (EUS), also known as mycotic granulomatosis. In this study, interspecific relationships were examined between A. invadans isolates and other aquatic animal pathogenic Saprolegniaceae, and saprophytic Saprolegniaceae from EUS-affected areas. Restriction fragment length polymorphisms and sequences of ribosomal DNA confirmed that A. invadans is distinct from all other specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…The agreement between the FISH and PCR assays indicates that PCR alone could be used as a reliable diagnostic test for the presence of A. invadans infection. In addition to this assay, other A. invadans PCR assays are available (3,26,38). Blazer et al (3) used PCR to assay an unspecified number of naturally infected, formalin-preserved fish from 13 UM epidemics to demonstrate the broad geographic range of A. invadans extending from the Indian River in Delaware to a farm pond in Louisiana.…”
Section: Discussionmentioning
confidence: 99%
“…The agreement between the FISH and PCR assays indicates that PCR alone could be used as a reliable diagnostic test for the presence of A. invadans infection. In addition to this assay, other A. invadans PCR assays are available (3,26,38). Blazer et al (3) used PCR to assay an unspecified number of naturally infected, formalin-preserved fish from 13 UM epidemics to demonstrate the broad geographic range of A. invadans extending from the Indian River in Delaware to a farm pond in Louisiana.…”
Section: Discussionmentioning
confidence: 99%
“…Aphanomyces is a genus that includes many important pathogens of crustacea (e.g., Aphanomyces astaci; Dykstra et al, 1986), fish (e.g., Aphanomyces invadans; Lilley et al, 2003), and plant roots (e.g., A. euteiches; Johnson et al, 2002), which together with several genera of little studied soil/root inhabiting oomycetes, Plectospira, Pachymetra (Reithmu¨ller et al, 1999), and Verrucalvus (Thines unpublished data) form a well-supported clade that is separate from other members of the Saprolegniaceae (Fig. 1.3).…”
Section: A Place For the Water Molds -A Fishy Talementioning
confidence: 99%
“…This phenomenon has been observed in two species of fishes from excavated earthen pond at the western shore of the Suez Canal, Egypt, during the winter of 1971 (Shaheen et al, 1999). According to Lilley et al (2003) this invasive Aphanomyces fish infection has been reported by Shaheen et al (1999) and has been caused by A. invadans species. It has also been observed on skin-muscles on aquarium species of Labeo bicolour Smith specimens and on the alevins of the Nile tilapia-Oerochromis niloticus L.…”
Section: Discussionmentioning
confidence: 69%